2021
DOI: 10.3390/nu13082638
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Western and Mediterranean-Type Diets on Gut Microbiota: A Metagenomics and Metabolomics Approach

Abstract: Our aim was to determine the effect of diet on gut microbiota, digestive function and sensations, using an integrated clinical, metagenomics and metabolomics approach. We conducted a cross-over, randomised study on the effects of a Western-type diet versus a fibre-enriched Mediterranean diet. In 20 healthy men, each diet was administered for 2 weeks preceded by a 2-week washout diet. The following outcomes were recorded: (a) number of anal gas evacuations; (b) digestive sensations; (c) volume of gas evacuated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 38 publications
4
51
0
Order By: Relevance
“…The volume of gas within the colon, measured by magnetic resonance, remained constant before and during FMP consumption. This observation, i.e., the effect of the FMP on gas metabolism, without changes in the colonic gas content, is in accordance with previous studies that showed no differences in intracolonic gas volume with dietary interventions that modified gas production [16,17]. Indeed, the gas content is under tight homeostatic control at around 100-200 mL.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The volume of gas within the colon, measured by magnetic resonance, remained constant before and during FMP consumption. This observation, i.e., the effect of the FMP on gas metabolism, without changes in the colonic gas content, is in accordance with previous studies that showed no differences in intracolonic gas volume with dietary interventions that modified gas production [16,17]. Indeed, the gas content is under tight homeostatic control at around 100-200 mL.…”
Section: Discussionsupporting
confidence: 92%
“…It has been documented that, as compared to a low-residue diet, a high-residue diet increases both the volume of colonic biomass and faecal clearance, conceivably by an increase in the residue load and microbiota proliferation [16,17]. FMP administration may have moderated this effect, but biomass volumes and faecal weight were not measured in the present study, and we cannot determine whether the effect of the FMP on symptoms was related to the downregulation of biomass proliferation.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The volume, production, and elimination of intestinal gas are well understood, and it is also known that the composition of the gas evacuated per anus reflects the metabolic activity of intestinal microbiota [ 1 , 2 , 3 ]. However, despite multiple reports relating the volatilome of feces with several pathologies [ 4 , 5 , 6 , 7 ], the composition of intestinal gas in normal conditions is poorly explored.…”
Section: Introductionmentioning
confidence: 99%